Community Based Tourism : Strategi Wujudkan One Village One Destination Melalui Program Wisata Desa Kampung Bawang Merah Purworejo - Siska Nurnaningati; Irvan Pratama; Cesya Rizkika Parahiyanti (Jurnal Nusantara Berbakti, 2023)
Rural economic development aims to create an environment that allows people to have a high life expectancy. The Malang Regency Government has launched the One Village One Destination program which demands that every village can produce competitive tourism products by utilizing local resources. Purworejo Village is a village located in Ngantang District with the majority of their livelihood being shallot farmers. Purworejo village was also crowned as a national model village producing high quality shallots, so many elements of society visited to learn about shallot management. The natural beauty and original culture of the village are additional potential that can be managed further to support the realization of Kampung Bawang Merah Village Tourism. The method used in this mentoring is a classical and individual approach. The subjects of this activity were 45 people from the Farmer's Group, PKK Mothers, youth organizations and the village government. The socialization and training participants received the results of this activity well. The results of this training will be used as a reference in preparing to develop human resources in managing tourist attractions and collaborating with partners as an embodiment of the Community Based Tourism (CBT) strategy.